Informação agropecuária no Panamá: caracterização do usuário e o potencial informativo - Castillo Sánchez, Octavio (1983)
The agricultural information user in Panama was described and the information infrastructure of this area was studied. The self-administered questionnaire technique for users (present and potential) and for librarians, was utilized. One hundred and seventy four (174) questionnaires were distributed to 23 per cent of a group of users numbering seven hundred and forty one (741) assigned to the eight(8) institutions comprising the Panamanian agricultural sector in Panama City, Veraguas, Chiriqui and Herrera. One hundred and twelve (112) user questionnaires were returned representing 15 per cent of total users and 64 per cent of the sampling In addition, ten (10) questionnaires were sent to librarians or to the person in charge of the library in eight (8) institutions, while three (3) have no library and three(3) of failed to return them It was concluded that libraries in this sector have a poor infrastructure. Analysis of user questionnaires allowed classifying users as to information needs, productivity and use of information channels and sources.